Nanosponge: An Overview - Raut, Poonam; Bhosale, Nikita; Joshi, Varda (Asian Journal of Pharmaceutical Research and Development, 2023)
The "Pharmaceutical Nanotechnology" subfield of pharmaceutical sciences, which is now in its infancy, offers new tools, prospects, and horizons with potential applications in the field of therapy and diagnostics of disease. Pharmaceutical nanotechnology consists of items that are nanosized and may be altered in many ways to enhance their properties. According to the administration method, the nanoporous particles are NSs that may entangle a wide variety of materials before being absorbed into a suitable formulation. They delay the drug's release in a regulated manner, stop the drug's protein from degrading, and disperse the drug where it is needed. They can move about the body, connect to the skin, and release the medicine at the intended target spot in a regulated and predictable way. They have excellent aqueous solubility, making them a carrier for medications with poor water solubility. When compared to other nanocarriers, they have greater drug loading capabilities. They are therefore appropriate for addressing issues with active ingredient stability, solubility, and delayed release. The main benefit of nanosponges of weakly water soluble medicines. They can function as biocatalysts in the administration of enzymes, proteins, vaccines, and antibodies and can administer medications via a variety of routes, including oral, topical, parental, etc.